Correlates of aspirations of Muslim Filipinos implications for educational and other government policies - Dindang, Norlain
Survey and ethnographic futures research techniques were conducted among 615 Muslim Filipinos drawn by stratified and simple random sampling of households in Lanao del Sur, Maguindanao, and Sulu where majority of the Maranaos, Maguindanaos, and Tausugs reside. Muslims in the Philippines have economic, political, and social aspirations for themselves, for their community, and for nature. Economically, they aspire for food, income, house and lot, employment and well-planned environment. Politically, they aspire for peace and order, freedom, honest elections, dignity, and leadership. Socially, they stress self satisfaction, happy family life, education, physical health, and religious standards. Their aspirations are a function of their ethnic identity, age, sex, education, employment, occupation, and family income.